2017
DOI: 10.1186/s12896-017-0388-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vitreoscilla hemoglobin enhances production of arachidonic acid and lipids in Mortierella alpina

Abstract: BackgroundArachidonic acid (ARA, C20:4, n-6), which belongs to the omega-6 series of polyunsaturated fatty acids and has a variety of biological activities, is commercially produced in Mortierella alpina. Dissolved oxygen or oxygen utilization efficiency is a critical factor for Mortierella alpina growth and arachidonic acid production in large-scale fermentation. Overexpression of the Vitreoscilla hemoglobin gene is thought to significantly increase the oxygen utilization efficiency of the cells.ResultsAn opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Dissolved oxygen-limiting conditions affect not only cell growth but also the production of metabolit. It has been reported previously that VHb enhances ATP production and respiratory activity [38,42]. This study has shown that the expression of VHb increased the yield of vitamin E, especially under oxygen-limiting conditions.…”
Section: Resultssupporting
confidence: 63%
“…Dissolved oxygen-limiting conditions affect not only cell growth but also the production of metabolit. It has been reported previously that VHb enhances ATP production and respiratory activity [38,42]. This study has shown that the expression of VHb increased the yield of vitamin E, especially under oxygen-limiting conditions.…”
Section: Resultssupporting
confidence: 63%
“…The expression of an optimized VHb gene generated 4‐ and 8‐fold increase in total lipid and arachidonic acid (ARA) yield than the M. alpina wild‐type strain under a microaerobic environment, and 1·6‐fold increase of ARA production in common growth condition (Zhang et al . ). In this study, Y. lipolytica mutant with VHb expression similarly enhanced the TFA content under five DO levels compared with the control strain, and TFA content was increased by 38·69% when DO concentration was controlled at 30%.…”
Section: Resultsmentioning
confidence: 97%
“…; Zhang et al . ). In this study, VHb was expressed in Y. lipolytica and its effect on cell growth and lipid accumulation was investigated.…”
Section: Introductionmentioning
confidence: 97%
“…The results are in good agreement with previous reports of fungi, where increased levels of biomass and metabolite yields were associated with heterologous expression of VHb. For instance, threefold elevated levels of α-amylase and a 31% increase in the total secreted protein by VHb-expressing Schwanniomyces occidentalis under oxygen-limiting environment (Suthar and Chattoo 2006 ), increased biomass, glucose uptake rate, glycerol production rate, specific oxygen uptake rate and CO 2 production rate by Aspergillus niger (Hofmann et al 2009 ), improved biomass and protein production by Aspergillus sojae (Mora-Lugo et al 2015 ), increased biomass and arachidonic acid production by Mortierella alpine (Zhang et al 2017 ), these results were all obtained when engineering these filamentous fungi with VHb. The presence of VHb did not significantly affect cell growth in Ganoderma lucidum (Li et al 2016b ) and Pseudomonas aeruginosa (Geckil et al 2001 ).…”
Section: Discussionmentioning
confidence: 99%